2014
DOI: 10.1016/j.bcp.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin inhibits human melanoma cell growth through direct binding to p70S6K and mTOR: Findings from 3-D melanoma skin equivalents and computational modeling

Abstract: The incidence of melanoma continues to rise. Inspite of treatment advances, the prognosis remains grim once the disease has metastasized, emphasizing the need to explore additional therapeutic strategies. One such approach is through the use of mechanism-based dietary intervention. We previously showed that the flavonoid fisetin inhibits melanoma cell proliferation, in vitro and in vivo. Here, we studied fisetin-mediated regulation of kinases involved in melanoma growth and progression. Time-course analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 27 publications
0
57
0
Order By: Relevance
“…We previously showed that the dietary flavonoid fisetin decreased Mitf levels in 451Lu melanoma cells through interference with Wnt/β-catenin signaling and inhibited tumor growth in a xenograft model (20). Employing cell free systems and 3-D melanoma skin equivalent constructs, we next demonstrated, that fisetin binds with much higher affinity to p70S6K and mTOR in comparison to AKT, to execute its growth inhibitory effect on cancer cells (27). The aim of the current study was to further dissect the molecular and biochemical pathways activated in fisetin-induced cytotoxicity and subsequent growth inhibition in human melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that the dietary flavonoid fisetin decreased Mitf levels in 451Lu melanoma cells through interference with Wnt/β-catenin signaling and inhibited tumor growth in a xenograft model (20). Employing cell free systems and 3-D melanoma skin equivalent constructs, we next demonstrated, that fisetin binds with much higher affinity to p70S6K and mTOR in comparison to AKT, to execute its growth inhibitory effect on cancer cells (27). The aim of the current study was to further dissect the molecular and biochemical pathways activated in fisetin-induced cytotoxicity and subsequent growth inhibition in human melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…We had reported previously that fisetin negatively regulated the growth of human melanoma cells through disruption of Wnt/β-catenin signaling and decreased Mitf levels [31]. We extended these studies in melanoma cells and evaluated the relative binding affinities of fisetin to kinases involved in growth and proliferation [32]. Our studies in melanoma monolayers and 3D melanoma skin equivalent model demonstrated that fisetin targets p70S6K and mTOR (Figure 1) and exerts an inhibitory effect on the growth of human melanoma cells through direct binding to these kinases [32].…”
Section: Anti-cancer Activity Of Fisetinmentioning
confidence: 99%
“…We extended these studies in melanoma cells and evaluated the relative binding affinities of fisetin to kinases involved in growth and proliferation [32]. Our studies in melanoma monolayers and 3D melanoma skin equivalent model demonstrated that fisetin targets p70S6K and mTOR (Figure 1) and exerts an inhibitory effect on the growth of human melanoma cells through direct binding to these kinases [32]. Interestingly, fisetin was found to have a very low binding affinity to Akt suggesting that the decreased phosphorylation of Akt observed upon fisetin treatment was mediated through its effect on interrelated pathways [32].…”
Section: Anti-cancer Activity Of Fisetinmentioning
confidence: 99%
See 1 more Smart Citation
“…Fisetin treatment also promoted mesenchymal to epithelial transition (MET) by decreasing mesenchymal marker proteins and increasing epithelial marker proteins [108]. Syed et al [111, 112] observed downregulation of Wnt/β-catenin, PI3K/AKT, mTOR, and microphthalmia-associated transcription factor (MITF) signaling proteins in melanoma cell lines and in a three-dimensional human skin equivalent melanoma model. These findings show that fisetin is a phytochemical with promising anti-melanoma activities.…”
Section: Phytochemicals For the Prevention/treatment Of Melanomamentioning
confidence: 99%